Well-controlled atom transfer radical polymerizations of acrylates using recyclable niobium complex nanoparticle as photocatalyst under visible light irradiation. (20th March 2015) - Cao, Yanlin; Xu, Yuanhong; Zhang, Jizhen; Yang, Dongjiang; Liu, Jingquan
Abstract: Niobium complex was successfully introduced into atom transfer radical polymerization (ATRP) system as a new kind of recyclable photocatalyst. The niobium complex acted as photocatalyst that could be activated by the photoredox reaction under visible light irradiation and ethyl 2-bromoisobutyrate (EBiB) was used as initiator. Successful ATRP polymerizations of acrylates were realized. The well-defined polymers with controlled molecular weight and narrow polydispersity index (PDI) (Mw /Mn = 1.16–1.30) could be achieved when the feed ratio of photocatalyst to EBiB was controlled properly. It was also found that the polymerization is highly responsive to light initiation, therefore, the polymerization can be controlled on or off at ease. In addition, the photocatalyst can be recycled and reused to initiate the polymerization for many times without significant compromisation of the initiation efficiency. Graphical abstract: Highlights: Niobium Complex as visible light photocatalyst was introduced into ATRP system. Well-defined polymers of acrylates could be achieved at proper feed ratio of photocatalyst to initiator. Niobium complex can be recycled and reused for many times.